The role of liver resection in metastatic nephroblastoma: a systematic review and Meta-regression analysis - Fuchs, Juri; Murtha-Lemekhova, Anastasia; Kessler, Markus; Günther, Patrick; Hoffmann, Katrin (BMC cancer, 2022)
Background: The impact of hepatic resection for liver metastases (LM) on the survival of pediatric patients with Wilms' tumor (WT) is unclear. So far, there is a lack of studies investigating the best suited treatment for patients with WTLM, and the role of liver resection has rarely been investigated. Thus, the development of evidence-based guidelines concerning indications of liver resection for WTLM remains difficult. Aim: To investigate the role of surgery in the therapy of WTLM. All available data on liver resections and subgroup outcomes of patients with WTLM are analyzed. Main research question is whether liver resection improves survival rates of patients with WTLM compared to non-surgical treatment. Methods: A systematic literature search of MEDLINE, Web of Science, and Central provided the basis for this PRISMAcompliant systematic review. For the main analysis (I), all studies reporting on surgical treatment of pediatric WTLM were included. To provide a representative overview of the general outcome of WTLM patients, in analysis II all studies with cohorts of at least five WTLM patients, regardless of the kind of treatment, were reviewed and analyzed. A Multiple meta-regression model was applied to investigate the impact liver resection on overall survival. Results: 14 studies with reports of liver resection for WTLM were found (Analysis I). They included a total of 212 patients with WTLM, of which 93 underwent a liver resection. Most studies had a high risk of bias, and the quality was heterogenous. For the analysis II, eight studies with subgroups of at least five WTLM patients were found. The weighted mean overall survival (OS) of WTLM patients across the studies was 55% (SD 29). A higher rate of liver resection was a significant predictor of better OS in a multiple meta-regression model with 4 covariates (l2 29.43, coefficient 0.819, p = 0.038). Conclusions: This is the first systematic review on WTLM. Given a lack of suited studies that specifically investigated WTLM, ecological bias was high in our analyses. Generating evidence is complicated in rare pediatric conditions and this study must be viewed in this context. Meta-regression analyses suggest that liver resection may improve survival of patients with WTLM compared to non-surgical treatment. Especially patients with persisting disease after neoadjuvant chemotherapy but also patients with metachronous LM seem to benefit from resection. Complete resection of LM is vital to achieve higher OS. Studies that prospectively investigate the impact of surgery on survival compared to non-surgical treatment for WTLM are highly needed to further close the current evidence gap.
Gesehen am 02.02.2022